2016
DOI: 10.1038/jhh.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery in hypertensive patients: relationship with blood pressure control

Abstract: Delayed heart rate recovery (HRR) post treadmill exercise testing reflects autonomic dysfunction and is related to worse cardiovascular outcome. The present study compared HRR in normotensive subjects and hypertensive patients taking anti-hypertensive medications with controlled blood pressure (BP) and uncontrolled BP. A total of 279 consecutive patients with (n=140, HP) and without (n=139, N-HP) essential hypertension who were hospitalized in our department during May 2012 to March 2016 were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…Another study [11] reported that heart rate was increased and HRV was decreased in patients with refractory hypertension, suggesting that overactivation of the sympathetic nervous system might play an important role in patients with refractory hypertension. In a previous study [12], we demonstrated significant differences on autonomous balance in hypertensive patients with controlled and uncontrolled blood pressure. The present study showed that TS (reflecting vagus function triggered by endogenous ventricular premature beat [13]), rMSSD (reflecting vagus function by external environmental stimuli [14]), pNN50 (reflecting vagus function by external environmental stimuli [14]), VLF (reflecting sympathetic activity by external environmental stimuli [15]), LF (reflecting balance of sympathetic and vagal activity [14]), and HF (reflecting vagus function by external environmental stimuli [14]) values were significantly lower in hypertensive patients compared to N-HP patients, and TS, rMSSD, pNN50, VLF, LF, and HF values were also significantly lower in hypertensive patients with uncontrolled blood pressure compared to hypertensive patients with controlled blood pressure.…”
Section: Discussionmentioning
confidence: 78%
“…Another study [11] reported that heart rate was increased and HRV was decreased in patients with refractory hypertension, suggesting that overactivation of the sympathetic nervous system might play an important role in patients with refractory hypertension. In a previous study [12], we demonstrated significant differences on autonomous balance in hypertensive patients with controlled and uncontrolled blood pressure. The present study showed that TS (reflecting vagus function triggered by endogenous ventricular premature beat [13]), rMSSD (reflecting vagus function by external environmental stimuli [14]), pNN50 (reflecting vagus function by external environmental stimuli [14]), VLF (reflecting sympathetic activity by external environmental stimuli [15]), LF (reflecting balance of sympathetic and vagal activity [14]), and HF (reflecting vagus function by external environmental stimuli [14]) values were significantly lower in hypertensive patients compared to N-HP patients, and TS, rMSSD, pNN50, VLF, LF, and HF values were also significantly lower in hypertensive patients with uncontrolled blood pressure compared to hypertensive patients with controlled blood pressure.…”
Section: Discussionmentioning
confidence: 78%
“…Previous report described delayed HRR and abnormal HRV in DM patients [2,19]. Reduced HRR reflected impaired vagal functional status after exercise [23]. SDNN reflects total sympathetic and vagal functional status [9].…”
Section: Discussionmentioning
confidence: 93%
“…Treadmill exercise testing was performed according to the exercise test guideline of the American College of Cardiology/American Heart Association [22] with GE T2100 treadmill system (General Electric Company, Boston, USA) as previously described [23]. Briefly, Bruce exercise plan was used and all subjects achieved submaximal goal heart rate [(220-age) * 0.85].…”
Section: Treadmill Exercise Testing and Hrr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…9 More hypertension in the abnormal HRR group was in accordance with studies that reported hypertension was more common in the abnormal group. 11 More smoking in the normal HRR group. This result contrasts with studies reported more smoking in the abnormal HRR group.…”
Section: Discussionmentioning
confidence: 98%